Incidence and Predictors of Contrast Induced Nephropathy after Coronary Intervention at College of Medical Sciences Teaching Hospital, Bharatpur - Sharma, Sanjib Kumar; Dubey, Laxman; Laudary, Shankar; Dhungel, Sachin; Ghimire, Madhav; Pahari, Bishnu; Gautam, Samir; Guruprasad, Sogunuru; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Background and Aims: The implications of radio-contrast induced nephropathyare disastrous. In Nepal there is scarcity of data on contrast induced nephropathy. This observational descriptive study was undertaken to study the incidence of contrast induced nephropathy and to identify risk factors (predictors) for the development of contrast induced nephropathy in patients undergoing coronary angiography and angioplasty in atertiary care hospital. Methods: The subject consists of 540 patients undergoing coronary intervention from 2011 to 2013 were enrolled by convenient sampling technique. Two hundreds ten patients were excluded from the study. Therefore, a total of 330 patients were studied and analyzed. Contrast induced nephropathy was defined as an increase of >25% or >0.5 mg/dl in pre-catheterization serum creatinine at or after 48 h after percutaneous coronary intervention. Estimated glomerular filtration rate as calculated by applying the 4 variables Modification of Diet in Renal Disease Study equation. Standard definitions were used to define the variables. Results: Twenty seven (8.18%) patients experienced contrast induced nephropathy. The incidence of contrast induced nephropathy in patients with baseline creatinine clearance